How Stigma Surrounding the Use of HIV Preexposure Prophylaxis Undermines Prevention and Pleasure: A Call to Destigmatize “Truvada Whores” - Calabrese, Sarah K. (Am J Public Health, 2015)
Antiretroviral preexposure prophylaxis (PrEP; emtricitabine and tenofovir disoproxil fumarate [Truvada]) prevents HIV without penalizing sexual pleasure, and may even enhance pleasure (e.g., by reducing HIV-related anxiety). However, concern about sexual risk behavior increasing with PrEP use (risk compensation) and corresponding stereotypes of promiscuity may undermine PrEP’s preventive potential. In this commentary, we review literature on sexual behavior change accompanying PrEP use, discuss risk compensation concerns and the “Truvada whore” stereotype as PrEP barriers, question the appropriateness of restricting PrEP access because of risk compensation, and consider sexual pleasure as a benefit of PrEP, an acceptable motive for seeking PrEP, and a core element of health. It is essential for science to trump stereotypes and sex-negative messaging in guiding decision-making affecting PrEP access and uptake.